Notes on the Moroccan Sensorium - Griffin, Kit (Anthropologica, 2022)
This research note begins by setting out the received wisdom concerning the structure and content of knowledge in oral as opposed to literate societies. I then proceed to analyze some of the stereotypes which inform that wisdom from the perspective of Bourdieu’s notion of the "habitus." The major part of the essay is devoted to showing how the notion of the "habitus" helps to explain the patterning of oral, visual and tactile knowledge and communication in Morocco.